Analysing the Validity of Misconceptions about Open and Distance Learning among High school teachers in Mashonaland Central Province of Zimbabwe - Kasowe, Rittah (IJRDO- Journal of Educational Research, 2017)
This study identifies a set of misconceptions about distance education among high school teachers in Mashonaland Central of Zimbabwe. These misconceptions were verified quantitatively with 60 systematic randomly selected high school teachers who guide students on tertiary enrolment selection. Data were collected using questionnaire and interview and analysed using simple percentages and content analysis. The findings showed that the misconceptions which had higher ranking values among the respondents were: ODL is an opportunistic form of learning for average or less intelligent students (60 or 100%); ODL as a mode of learning with low quality assurance (58 or 96.7%); ODL as inferior form of learning since it is technologymediated (56 or 93.3%) and less vigorous in comparison with the conventional mode of learning (56 or 93.3%). The study recommended, among others, that marketing and workshops should be organized for high school teachers, and high school students on the importance of distance learning at tertiary level.